PENGARUH JUMLAH ANGGOTA DAN STRUKTUR MODAL KOPERASI TERHADAP JUMLAH SISA HASIL USAHA PADA KOPERASI PEGAWAI REPUBLIK INDONESIA DI PURWOKERTO - Lutfan Haidi; Eliada Herwiyanti; Permata Ulfah (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2021)
The purpose of this study was to determine the effect of the number of members and the capital structure of cooperatives on the amount of Remaining Operations (SHU) on the Cooperative of Employee Republic of Indonesia (KPRI). Samples of 15 KPRI in Purwokerto were obtained by purposive sampling technique. Based on 3 years of observation, the amount of research data is 45. Furthermore, the data were analyzed using panel data regression analysis techniques. The results showed that: (1) The number of members had no effect on SHU; (2) Own capital has a positive effect on the Remaining Results of Operations; and 3) Loan capital has no effect on the Remaining Results of Business. Theoretically, this research only supports the theory of stewardship in terms of own capital. Whereas in terms of number of members and no loan capital, this is because the cooperative managers are none other than a small number of existing members so the existence of loan capital is not a priority to be managed. Practically, this research can be considered for cooperative managers and cooperative members to better manage cooperative cooperatives through increasing the number of members, and utilizing their own capital and existing loan capital. Furthermore, the government is expected to be able to pay more attention and supervise cooperatives so that their existence benefits the Indonesian people.